Concept of Climate Vulnerability: Key Determinants, Responses and Constraints to Climate Change Adaptation. - Sarfo, Isaac; Boakye Yiadom, Michael; Dontoh, Jude Issa (Advances in Social Sciences Research Journal, 2019)
The paper is essentially a synthesis report highlighting key areas of climate vulnerability as a global discourse based on reports from international conventions held over the years. Theoretically, it draws country and sector based scenarios on responses and constraints to climate adaptation. The literature is organized in phases, constituting a conceptual framework, evidence and trend of climate impacts, local ecosystem-based approach (EbA) to sustainable adaptation models, espoused across climate-sensitive sectors. The ultimate aim of this paper is to synthesize and develop a synthesis report on key determinants of climate vulnerability based on existing literature.